Astrocytic spermidine insufficiency contributes to enhanced pain sensitivity associated with ApoE4 - Kaiming Yu; Xiongyao Zhou; Baolong Li; Jialu Sun; Tuo Yang; Weizhen Li; Ningning Wang; Xiaosong Gu; Shusen Cui; Rangjuan Cao (The Journal of Headache and Pain)
Abstract Neuropathic pain is a chronic condition with limited effective treatments, closely associated with astrocytes and their role in central sensitization. Apolipoprotein E (ApoE), predominantly expressed in astrocytes in central nervous system, exists in three ApoE isoforms (ApoE2, ApoE3, and ApoE4) in humans, with ApoE4 linked to increased susceptibility to neurological diseases. However, the relationship between ApoE4 and neuropathic pain, as well as underlying mechanisms, remains poorly understood. Here, we demonstrated that mice expressing human ApoE4 (ApoE4-TR) displayed increased pain sensitivity following spared nerve injury (SNI) compared to ApoE3-TR mice. This increased sensitivity was also observed in mice with astrocyte-specific expression of ApoE4, achieved through Cre-mediated recombination. Metabolomic profiling revealed reduced spermidine levels in the spinal dorsal horn of ApoE4-TR mice relative to ApoE3-TR mice. Daily gavage administration of spermidine alleviated mechanical pain to a comparable level in ApoE3-TR and ApoE4-TR mice, as assessed by von Frey test. However, lower dose of spermidine effectively alleviated neuropathic pain in ApoE3-TR mice but showed reduced efficacy in ApoE4-TR mice, likely due to limited spermidine retention in ApoE4 astrocytes, as demonstrated in vitro. Transcriptomic analysis identified Nos2 as a critical gene upregulated in ApoE4-TR mice. Mechanistically, spermidine suppressed Nos2 expression by inhibiting the NF-κB pathway in astrocytes, thereby alleviating neuropathic pain. These findings highlight an enhanced pain sensitivity associated with ApoE4 and suggest spermidine as a potential therapeutic strategy, emphasizing a tailored dosage approach for ApoE4 carriers.